Exploration of the impact of gender biased texts in physical sciences GAPS document on grade 12 female learners in Mogodumo Circuit, Limpopo Provice - Chuene, Elisa Sebina (My University, 2021)
Background: Gender bias in the Physical Sciences education favours male learners to the disadvantages of female learners, bringing along sex discrimination. Physical Sciences Curriculum reinforces masculinity, resulting in few females enrolling for science-related subjects. Male learners outperform female learners in Physical Sciences. Also, sex discrimination due to gender bias is visible in the workforce in the fields of Science, Technology, Engineering and Mathematics. Therefore, the purpose of this study was aimed at exploring gender biased texts in the Physical Sciences CAPS document and also its impact on Grade 12 female learners. Method: A qualitative exploratory phenomenological study design was conducted. In my study, participants were Physical Sciences Grade 12 female learners and their teachers. The total number of participants was 12 (8 female learners and 4 teachers) and the sample depended on data saturation. Also, data were collected using document review (Physical Sciences Curriculum and AssessmentPolicy Statements document and prescribed textbook), classroom observation and interviews with learners and teachers. One-on-one interviews were conducted with participants using interview guides for both teachers and learners. Data collected from interviews were analysed using thematic 8 steps of Tesch’s inductive and descriptive open coding technique. Results: The results from the document review showed the existence of gender bias in the Physical Sciences textbooks and Curriculum and AssessmentPolicy Statement document. Classroom observation showed that male learners were more interested and participated actively in the Physical Sciences lesson as compared to female learners. Both teachers and learners are aware of the existence of gender biased texts in Physical Sciences education. Further, this impacts negatively towards female learners leading to a bad attitude towards sciences and subsequently, to poor performance as compared to male learners. Female learners believe that they were to perform better in Physical Sciences if they were of the male gender. Conclusion: The existence of gender biased texts in the Physical Sciences Curriculum and Assessment Policy Statements document and prescribed textbooks reinforce masculinity in the field. There is a need to review the Physical Sciences Curriculum and Assessment Policy Statement document and prescribed textbooks to ensure inclusivity, eliminate sex discrimination and also to achieve balance in the workforce in the science field. Key concepts Physical Sciences; Curriculum and Assessment Policy Statements; Female learner; Gender Biased texts; Performance; Inclusive education
Thesis (M. Ed. (Curriculum Studies)) -- University of Limpopo, 2021
Keywords: Physical Sciences; Curriculum and Assessment Policy Statements; Female leaner; Gender Biased texts; Performance; Inclusive education; Test bias -- South Africa; Education -- South Africa; Sex discrimination in education; Sexism in textbooks